Studi In silico Potensi Anti Hipertensi dan Prediksi Profil Farmakokinetika Daun Jati Belanda (Guazuma ulmifolia. Lamk) - Andri Tilaqza; Merlita Herbani (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2021)
Abstract. Hypertension is a disease that is often occurred in every country, including Indonesia. Hypertension is one of the risk factors that lead to cardiovascular disease. Guazuma ulmifolia Lamk are one of the plants used empirically as antihypertensive in Indonesia, but research on the antihypertensive potential of its leaves has never been done before.The purpose of this study was to predict the potential activity and predict the pharmacokinetic of several compounds contained in Guazuma ulmifolia leaves. The Guazuma ulmifolia leaves compounds and captopril were docked to the Angiotensin-Converting Enzyme protein (PDB ID: 1O86). Molecular docking tests were performed using PyRx software while the visualization analysis of molecular anchoring results was performed using Biovia Discovery Studio Visualizer software. Prediction of pharmacokinetic and physicochemical properties of the tested compounds was carried out using the pkCSM web page. Based on the molecular docking test, all compounds in Guazuma ulmifolia leaves have lower energy than the captopril. Kaempferitrin (-9.9 k/mol) and beta-sitosterol (-9.2 kcal/mol) had the lowest energy among other test compounds compared to captopril (-5.5 kcal/mol). Quercetin, kaempferol, and beta-caryophyllene were compounds that had similar interactions to the captopril based on the chemical interaction. All compounds had varied pharmacokinetic profiles but still had a fairly good profile.